Development and validation of an aetiology in delirium diagnostic support tool. (10th December 2020) - Eeles, Eamonn; Huang, Lisa; Dakin, Lucy; Ling, Carolina; Dunn, Erin; Fraser, Jon; Dissanayaka, Nadeeka N
Abstract: Background: recognition of the multifactorial causes of delirium represents a clinical challenge. Objectives: to develop and show proof of principle of a diagnostic support tool (DST) for identification of causes of delirium. Methods: stage 1—development of the aetiology in delirium-diagnostic support tool (AiD-DST); stage 2—validation of the AiD-DST against reference standard diagnosis, based on clinical assessment from two independent consultant geriatricians. Results: a series of eight steps AiD-DST were formulated by an expert group to identify possible causes of delirium. Forty inpatients admitted to a general medical unit with a consultant physician/geriatrician diagnosis of delirium were recruited, consented and reviewed against the AiD-DST. Mean age was 85.1 (standard deviation 7.9) years and 26 (65%) of participants were female. Participants had multiple chronic co-morbidities [median Charlson Comorbidity Index 7; interquartile range (IQR 6–9)] and median number of medications was 8 (IQR 6–11.75). Median number of causes of delirium detected on AiD-DST was 3 (IQR 3–4) versus 5 (IQR 3–6) using the reference standard diagnosis, with sensitivity of 88.8% (95% confidence interval, 81.6–93.9%) and specificity of 71.8% (63–79.5%). Conclusions: the aetiology in delirium DST shows promise in the identification of cause(s) in delirium.